Rheumatic Heart Disease In Chad: Clinical, Paraclinical, Therapeutic And Progressive Aspects - Naibe, Dangwe Temoua; Ali, Adam Ahamat; Allawaye, Lucien; Doune, Narcisse; Adjougoulta, Koboy Allah Amine; Zakaria, Abdelmadjib; Langtar, Mianroh Hybi; Madjirangar, Natirngar; Dallah, Houba Urbain; Fatime, Abdoulaye; Binwe, Dikoua; Abdelkerim, Aboubakar; et al. (Journal of Hypertension and Cardiology, 2023)
Introduction Rheumatic heart disease is mostly common in low-income or developing parts of the world, such as Sub-Saharan Africa, with a high morbidity and mortality rate. There are few data that are available in Chad on rheumatic heart disease. Our objective was to study the clinical, echocardiographic, therapeutic, and progressive aspects of rheumatic heart disease at the Renaissance University Hospital Center and the National Reference Teaching Hospital in N’Djamena, Chad. Patient and methods This was a prospective, multicenter and observational cohort study, covering a consecutive series of patients consulted and/or hospitalized for rheumatic heart disease, documented by an echocardiogram from January 2015 to January 2021. Results Among the 4456 patients consulted and/or hospitalized, 398 cases of rheumatic heart disease (8.9%) were collected, and 364 patients had met the inclusion criteria. The mean age was 31.2 ± 14.4 years, and 193 patients (53%) were female. On admission, heart failure was present in 214 patients (58.8%), ischemic stroke in 10 patients (2.7%) and supraventricular arrhythmias such as atrial fibrillation in 94 patients (25.8%) and atrial flutter in 6 patients (1.6%). Mitral regurgitation was observed in 49.7% (n=181) of cases, aortic regurgitation in 33.2% (n=121), mitral stenosis in 31.3% (n=114), and aortic stenosis in 7.7% (n=28). At least two valvular disorders were combined in 48.4% of cases. A surgical intervention such as a heart valve replacement and/or valvuloplasty was performed in 80 patients (22.2%). At least one rehospitalization was noted in 56.9% of patients. Forty-two of the 150 patients free of heart failure at inclusion (28%) had experienced the first episode of decompensated heart failure during follow-up. On the other hand, in 119 patients (55.6%), it was the second episode of decompensated heart failure. Other progressive complications included atrial fibrillation (13.8%), thromboembolic complications (6.3%), infective endocarditis (6.0%) and prosthetic valve dysfunction (1.4%). Altogether, the mortality rate was 10.4%. It was 9.9% in non-operated patients compared to 12.5% in operated patients (p=0.49). Conclusion The present study shows that morbidity and mortality of rheumatic heart disease remain high in our context and often affect children, young adults, and women. Treatment is essentially based on cardiac surgery which is not available in Chad.
Keywords: Rheumatic heart disease; morbidity; mortality; Chad.